Metode Penalaran tentang Tuhan: Membaca Pemikiran 'Abdul Qahir al-Bagdadi (w. 429 H/ 1038 M) dalam Karyanya Kitāb Uṣūluddīn - Ryandi Ryandi; Amroeni Drajat; Abdullah bin Long (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2024)
The correct reasoning about God is important in Islamic faith. The value judgment of reasoning incorrectly about God is heresy. Al-Bagdadi was early Ash’arite (4th/5th AH), who compiled many correct reasoning arguments about God in his work Kitāb Uṣūluddīn. His arguments have influenced later Ash’arites such as Abu Muzaffar al-Isfaraini (w. 471 H/ 1078 M), Imam al-Haramain al-Juwaini (w. 478 H/ 1085 M), and Hujjatul Islam al-Gazali (w. 505/ 1111 M). This article explores al-Bagdadi's reasoning arguments elaborated in his work Uṣūluddīn, to then be reduced to the three methods of reasoning commonly used by the Ashharite, namely dalīl al-tamānu’, qiyās al-gayb ’alā al-syāhid, and al-sabr wa al-taqsīm. After analyzing his Uṣūluddīn, it is concluded that al-Bagdadi uses these three methods of reasoning in his description of God. Dalīl al-tamānu’ is used by al-Bagdadi to prove the oneness of God (waḥdāniyyah). Qiyās al-gayb ’alā al-syāhid is used to prove the existence of God, and the perfection of His attributes. As for al-sabr wa al-taqsīm is used to prove the truth of seeing God in the hereafter (ru'yatullāh), and the negation of limitations on the God. In addition to strengthening the Islamic faith with correct reasoning, the logical arguments built by al-Bagdadi are also intended to criticize deviant views of God, both from outside and internal Islam.  Because it is reason-based, its arguments are universally applicable.